Spin Doctor Role in Formation of Public Opinion Candidates for Mayor and Deputy Mayor of Kendari in Winning Local Elections [Peran Spin Doctor Dalam Pembentukan Opini Publik Kandidat Walikota dan Wakil Walikota Kendari Dalam Pemenangan Pemilihan Kepala Daerah] - Rivi Handayani (Jurnal Pekommas, 2013)
This study aims to identify and describe the role of the team's spin doctor in the image formation and communication strategies mayor and deputy mayor candidate Kendari through the mass media. The method uses descriptive quantitative research by making a systematic description, factual, and accurate based on facts and data populations in the field. The study was conducted over two months are May and June 2007 on all Kendari city's diverse society with different social and ethnic backgrounds who berbeda.Adapun population is 5 people on each campaign including open and closed successful team in question. To strengthen the formation of public opinion, it would require additional informants of some individuals and institutions associated such as: Candidates Mayor and Deputy City Kendari, Is Mass Media, Television, Radio, and Newspaper, Elite Political Parties and Election Commission. The results showed that the role of spin doctor in formulating a strategy based on SWOT analysis and image formation through print and electronic media is very influential and significant impact on the selection of candidates kemenagan Mayor and Deputy Mayor Kendari through political message to the community that are informative and persuasive.Penelitian ini didasarkan pada asumsi bahwa perlunya hak publik atas transparansi informasi dan entitas negara yang selalu mengandalkan adanya publik yang berdaulat. penyelenggaraan kekuasaan harus bersifat akuntabel, transparan dan aksesebel bagi publik. Penelitian ini menggunakan metode deskriktif dengan menggunakan pendekatan kualitatif. Sedangkan tipe penelitian ini menggunakan data kualitatif untuk menjelaskan fenomena yang sedalam-dalamnya melalui pengumpulan data dengan mengutamakan kualitas subjek penelitian. Hasil penelitian menunjukkan bahwa kehadiran kelompok dan tokoh masyarakat dalam memberikan sumbangsih pemikiran terkait dengan rancangan peraturan daerah tentang keterbukaan informasi publik menunjukkan adanya suara pro dan kontra untuk menjadikan Ranperda ini menjadi Perda.